Authentication study and implementation using IPSEC and IEEE 802.1X technology - Al-Amodi, Ahmed Omar (2009)
Researches in Information Technology have been subjected to a tremendous speed-up in recent years mainly due to the affordability of the technology and consequently, to a strongly increased interest of users. In addition, the security systems which imply networks have increased rapidly. Currently, many organizations provide extensive network services to their staff. This poses a problem of securing access to the organization networks. Therefore, authentication has become an inevitable reality in the design of such systems. The research sought for the best authentication mechanism suitable for organizations generally, and to university campuses, particularly. The result is an authentication scheme based on IPSec and IEEE 802.1x technology. The scheme provides secure access to users engaged in the network connection. It implements a two-factor authentication. The first factor is the network policy combination which the user provides prior logging onto the system. The second factor is the certificates that are stored locally in a client?s desktop/laptop. The mechanism involved in the authentication is based on EAP-TLS, which is a type of authentication method provided by IEEE 802.1x technology. The result of the implemented system is a highly secured scheme that provides both user and computer (machine) authentication. Only legitimate users with legitimate machines (computers) can access the organization network system in an authorized way.